The Possibility to Enhance the Quality of Built Environment by Densifying, Mixing and Compacting the Historical Area of Kota Tua Jakarta - Ari Widyati Purwantiasning; Saeful Bahri (Jurnal Permukiman, 2023)
This research is part of multi-year research, which is undertaken for two years. This research aims to analyze the possibility of applying three principles of Transit Oriented Development’s (TOD) concept. Those three principles are densifying, mixing, and compacting. By analyzing the option of applying those principles, it have been proposed the best solution to issues and problems within the historical area of Kota Tua Jakarta. The significance of this research is the historical area in Indonesia, particularly Jakarta Kota Tua, which has been regarded as a historical area within a metropolitan city. Since that the idea of TOD itself has been known as a perfect solution in some countries, particularly within metropolitan cities that have a relatively large population. This research has conducted the qualitative method using a case study as a way of thinking to get a clear description and fact. Kota Tua Jakarta has been designated as a case study because this area is one of the study significant historical regions in Jakarta. The result of this research will support another about the historical district and Transit-Oriented Development’s concept.